Predation of Desmodus rotundus Geoffroy, 1810 (Phyllostomidae, Chiroptera) by Epicrates cenchria (Linnaeus, 1758) (Boidae, Reptilia) in an Ecuadorian Cave - Sarah Martin-Solano; Theofilos Toulkeridis; Aaron Addison; Wilmer E. Pozo-Rivera (Subterranean Biology, 2016)
Bats are mammals of the Order Chiroptera. They are highly adaptable to several habitats and their ecology makes them vulnerable to predators. Bats are a common prey of snakes, but description of this kind of predation are rare. This study describes the event of predation of an Epicrates cenchria on a Desmodus rotundus, in a cave in Tena, Ecuador. Records of Desmodus rotundus are known from caves just as Epicrates cenchria. Castillo Cave has a total mapped length of 450 meters. The phase of constriction lasted for 10 min 2 s, a duration superior than other studies, due to the size of Desmodus rotundus. The terrestrial locomotion behavior of D. rotundus, makes it an easy target for E. cenchria. The predation event occurred on the floor, a rare case, which has not been described in other events of predation in caves. The cave is located in a disturbed habitat, because it is irrigated by wastewaters. But both species seems to be adapted to the environment. This study confirms that predation of bats in caves by snakes does occur.